Control of poly(N-isopropylacrylamide) microgel network structure by precipitation polymerization near the lower critical solution temperature - Hu, Xiaobo (Langmuir : the ACS journal of surfaces and colloids, 2011)
Poly(N-isopropylacrylamide) (pNIPAm) microgels were synthesized by precipitation polymerization at temperatures ranging from 37 to 45 °C using redox initiator system ammonium persulfate (APS)/N,N,N',N'-tetramethylethylenediamine (TEMED) or photoinitiator 2,2'-azobis(amidinopropane) dihydrochloride (V50). Photon correlation spectroscopy (PCS) and atomic force microscopy (AFM) studies revealed that spherical microgels with narrow size dispersities can be obtained with these methods and that the resultant microgels have volume phase transition behaviors expected from their compositions. Additionally, the low-temperature redox initiator strategy produces microgels devoid of self-cross-linking, thereby permitting the synthesis of completely degradable microgels when using N,N'-(1,2-dihydroxyethylene)bisacrylamide (DHEA) as a cleavable cross-linker. We also demonstrate the potential utility of the approach in bioconjugate syntheses; in this case, avidin immobilization is demonstrated by one-pot copolymerization at low temperature